2022
DOI: 10.3389/fimmu.2022.908173
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity With PD-1/PD-L1 Inhibitors in Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundPD-1/PD-L1 inhibitors have significantly improved the outcomes of those patients with various malignancies. However, the incidence of adverse events also increased. This meta-analysis aims to systematically evaluate the risk of cardiovascular toxicity in patients treated with PD-1/PD-L1 inhibitors.Materials and methodsWe searched PubMed, Embase, the Cochrane Library databases for all randomized controlled trials (RCTs) comparing all-grade and grade 3-5 cardiovascular toxicity of single-agent PD-1/PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 88 publications
4
13
0
Order By: Relevance
“…In this study, we also compared the risk of a CTLA-4 inhibitor combined with a PD-1/PD-L1 inhibitor to that with a PD-1/PD-L1 inhibitor alone. However, the incidence of cardiovascular toxicity was not increased with this combination, which was consistent with other trials [47,48]. There are several possible reasons why our results showed that combination therapy did not result in higher cardiovascular toxicity compared with monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we also compared the risk of a CTLA-4 inhibitor combined with a PD-1/PD-L1 inhibitor to that with a PD-1/PD-L1 inhibitor alone. However, the incidence of cardiovascular toxicity was not increased with this combination, which was consistent with other trials [47,48]. There are several possible reasons why our results showed that combination therapy did not result in higher cardiovascular toxicity compared with monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, ULCA significantly controls primary tumor growth in both ER/PR + breast cancer and TNBC xenograft mouse models and produces systemically detectable levels of encoded transgene IL-12p70. In previous studies, we detected CAdVEC-derived PD-L1 antibody at treated tumor sites but not in blood samples ( 6 ), suggesting that PD-L1 antibody produced by our CAdVEC will not lead to the systemic toxicities seen in patients systemically infused with immune checkpoint inhibitor (ICI) ( 14 ). To compare the benefits of CAdVEC (combination with OAd and HDAd) with single agents, we evaluated the toxicity, antitumor efficacy, and circulating IL-12p70 levels after low-dose (1 × 10 6 vp) and high-dose (1 × 10 9 vp) injection of single agents in the SUM-159 xenograft model (fig.…”
Section: Resultsmentioning
confidence: 78%
“…The different treatment regimens on the risk of dyspnea were presented for 19 incidence of dyspnea when compared with single ICI with moderate evidence of heterogeneity among the studies (I 2 = 41%) (Figure 5).…”
Section: Risk Of Dyspneamentioning
confidence: 99%
“…The different treatment regimens on the risk of pneumothorax were presented for 19 low evidence of heterogeneity among the studies (I 2 = 0% and 0%). Double ICIs (P = 0.99; SMD: 0.99; 95% CI: 0.17, 5.77) did not significantly change the incidence of pneumothorax when compared with single ICI with low evidence of heterogeneity among the studies (I 2 = 0%) (Figure 10).…”
Section: Risk Of Pneumothoraxmentioning
confidence: 99%
See 1 more Smart Citation